2018
DOI: 10.1016/j.resuscitation.2018.05.020
|View full text |Cite
|
Sign up to set email alerts
|

National early warning score (NEWS) in a Finnish multidisciplinary emergency department and direct vs. late admission to intensive care

Abstract: ED-NEWS is independently associated with in-hospital and 30-day mortality with acceptable discrimination capability. Direct and late ICU admissions occurred with comparable NEWSs at admission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 18 publications
1
48
0
Order By: Relevance
“…We analyzed the data by NEWS2 and triage category testing differences in 30- day mortality, ED LOS, hospital and ICU/HDU admission. For the clarity of presentation of the results for ED LOS, the NEWS2 were grouped into low (0–4), moderate [ 5 , 6 ] and high (> = 7), in line with the Royal College of Physicians guideline [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We analyzed the data by NEWS2 and triage category testing differences in 30- day mortality, ED LOS, hospital and ICU/HDU admission. For the clarity of presentation of the results for ED LOS, the NEWS2 were grouped into low (0–4), moderate [ 5 , 6 ] and high (> = 7), in line with the Royal College of Physicians guideline [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…The evidence for early warning scores at the emergency department so far is limited: studies mostly include small or pre-selected sub-cohorts. One recent study showed that the national early warning score (NEWS2) is independently associated with mortality and ICU admissions [ 5 ]. Another study found that the modified early warning score (MEWS) adequately predicted hospitalization and in-hospital mortality for the older adults in the emergency department [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The National Early Warning Score 1 (NEWS) and its modification, NEWS2 2 , are validated for the identification of patient deterioration in a range of clinical conditions and settings. 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 Both scores are advocated as screening tools for sepsis, 2 , 11 , 12 , 13 performing better than the quick Sequential (Sepsis-Related) Organ Failure Assessment (qSOFA) score 14 , 15 , 16 , 17 -a bedside prompt for identifying patients with suspected infection and a high risk of poor outcomes. 18 However, since the introduction of NEWS and NEWS2 in 2012 and 2017, respectively, the world has experienced an ongoing pandemic of a new infectious disease, coronavirus disease 2019 (COVID-19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the NEWS is associated with mortality and intensive care unit admission in patients admitted to the ED. [9][10][11][12] As mentioned above, the NEWS is based on the patient's vital signs. However, in elderly patients, mortality prediction based on vital signs may be difficult because older patients may show subtle changes in vital signs due to a reduced physiological response to physiological stress.…”
Section: Introductionmentioning
confidence: 99%